2002
DOI: 10.17221/4399-pse
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of DNA markers of potato (Solanum tuberosum ssp. tuberosum L.) resistance against Ro1 pathotype Globodera rostochiensis in selected F<sub>1</sub> progeny

Abstract: Marker assisted selection is the fast and objective method for detection of resistance major genes. This method is practical for identification of some candidate genes of quantitative resistance. Genetic markers based on Polymerase Chain Reaction (PCR) were used for evaluation of F 1 progenies Ornella × Mira and Tábor × Mira. Cultivar Mira has resistance against Ro1 pathotype G. rostochiensis. Cultivars Ornela and Tábor are susceptible to Ro1. Seedlings of F 1 generations were used for analyses. Plants were cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
0
9
0
2
Order By: Relevance
“…In other studies, marker CP113 showed either weak (Niewöhner et al, 1995) or good (Skupinová et al, 2002) diagnostic suitability. The markers U14 and X02 linked to the gene GroV1, marker 77R linked to Gpa2, marker TG432 associated with QTL conferring resistance to G. pallida and the SNP marker HC were unsuitable for diagnostic Markers 77R and HC are not presented because they were not detected in the parental forms of these tested clones purposes.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In other studies, marker CP113 showed either weak (Niewöhner et al, 1995) or good (Skupinová et al, 2002) diagnostic suitability. The markers U14 and X02 linked to the gene GroV1, marker 77R linked to Gpa2, marker TG432 associated with QTL conferring resistance to G. pallida and the SNP marker HC were unsuitable for diagnostic Markers 77R and HC are not presented because they were not detected in the parental forms of these tested clones purposes.…”
Section: Discussionmentioning
confidence: 76%
“…Nowadays the most widely used are CAPS and SCAR markers (Barone 2004). The following markers are recommended as a good tool for selection genotypes resistant to PCN: U14 and X02 (Jacobs et al 1996), CP113 (Niewöhner et al 1995, Skupinová et al 2002, TG689 (Sagredo et al 2004;Biryukova et al 2008), Gro 1,4 (Paal et al 2004;Gebhardt et al 2006), 77R (van der Voort et al 1999, SPUD1636 (Bryan et al 2002) and SNP marker named HC (Sattarzadeh et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian yang dilakukan oleh Colton et al (2006) menunjukkan bahwa dari total progeni kentang yang dievaluasi ketahanannya terhadap penyakit hawar daun, menghasilkan 25-50% progeni yang positif mengandung gen RB, yang berarti menunjukkan rasio segregasi dari 1 : 3 sampai 1 : 1. Segregasi marka DNA H1 pada tanaman kentang untuk ketahanan terhadap patotipe Ro1 Globodera rostochiensis pada progeni F 1 Tabor x Mira menunjukkan 50,22% mengandung gen H1 dan 49,78% tidak mengandung gen H1, sedangkan persilangan Ornella x Mira menghasilkan 56,16% progeni F 1 dengan gen H1 dan 43,84% tidak membawa gen H1 (Skupinova et al 2002).…”
Section: Analisis Pcr Gen Rbunclassified
“…One of the earliest markers to be developed for the H1 resistance gene, CP113, (Gebhardt et al. 1993) produced variable results, providing an effective predictor of PCN resistance within some germplasm sources (Skupinova et al. 2002, Dale et al.…”
mentioning
confidence: 99%
“…Unfortunately, to date, all markers identified as linked to the H1 resistance gene have displayed incomplete association of diagnostic alleles. One of the earliest markers to be developed for the H1 resistance gene, CP113, (Gebhardt et al 1993) produced variable results, providing an effective predictor of PCN resistance within some germplasm sources (Skupinova et al 2002, Dale et al 2006), but not others (Niewohner et al 1995, Hutchinson 1997, Milczarek et al 2011.…”
mentioning
confidence: 99%